Intravascular neoplastic cells in canine cutaneous plasmacytomas - Ehrensing, Gordon (J Vet Diagn Invest, 2018)
We evaluated 134 cutaneous plasmacytomas in 125 dogs submitted to the University of Tennessee surgical biopsy service between 2009 and 2012 to determine whether the presence of intravascular neoplastic cells had prognostic significance. Tumors occurred in middle-aged to geriatric dogs (range: 5–16 y, mean: 9.6 y) and most frequently involved the skin of the head and distal limbs. Diagnoses were made based on light microscopy, and in some cases confirmed by immunoreactivity of neoplastic cells for MUM1. Tumors were categorized as having or not having intravascular neoplastic cells within sections examined. The intravascular location of tumor cells was confirmed by immunoreactivity of endothelial cells for factor VIII–related antigen in 3 cases. Neoplastic cells within vessel lumens were identified in 20 of 125 dogs (16%). Submitting veterinary practices were contacted for follow-up data on patients including local recurrence and cutaneous plasmacytomas in other locations. Follow-up information was acquired on 99 dogs (79%). Recurrence was documented in one dog with cutaneous plasmacytomas; both masses had incomplete margins and intravascular neoplastic cells. Additional distant cutaneous plasmacytomas were later diagnosed in 3 patients; none of these dogs had intravascular neoplastic cells. In no cases were cutaneous plasmacytomas suspected to be a cause of death or reason for euthanasia. Intravascular neoplastic cells were more common in tumors of the distal limbs (36%) compared to other locations (11%; p = 0.0007). The presence of intravascular neoplastic cells did not affect prognosis in cutaneous plasmacytomas.